Speaking Against Inequity in the Writing Classroom: Challenging the Performance Paradigm for Undergraduate Oral Presentations - Luger, Moberley; Stensrud, Craig (Discourse and Writing/Rédactologie, 2022)
Many existing scholarly speaking pedagogies continue to think of oral presentations as performances for an audience rather than dialogic exchanges of research. Such approaches, prominent in Canadian universities, can exacerbate classroom inequities by valuing certain ways of speaking and, by extension, certain speakers: speaking pedagogies, for example, that instruct students to speak “clearly,” dress “professionally,” or even to appear “confident,” can encode prejudices that privilege some voices and bodies over others, perpetuating discrimination based on gender, race, sexuality, language, and culture. This article argues that an equitable scholarly speaking pedagogy will teach students to instead think of oral presentations as opportunities for collaborative knowledge-making. We offer strategies to help students think of scholarly speaking as an integral part of the research process, rather than a stand-alone performance. Drawing on genre-theoretical approaches to academic writing, we argue that this shift can be achieved by using “precedents”—examples of scholarly speaking—to familiarize students with academic oral discourse’s genre conventions, helping students to recognize scholarly speaking as a situated and dialogic research genre. By shifting the goal of academic oral presentations towards cooperative knowledge-making, these strategies at once challenge student prejudices about who can be a “good” speaker and remind students of their responsibilities as audience members, resulting in a more equitable and inclusive classroom environment. To provide a pragmatic example of our approach, we outline the “Classroom Conference” assignment that we developed and evaluated, which uses precedents to prepare students for the oral presentations that are integrated as a step in completing their larger research projects. Analyzing survey data from students who completed this assignment, we recognize its success but also propose strategies for overcoming persisting challenges in getting students to shift their thinking toward an equitable model of scholarly speaking.